SELF-ORGANIZED LEARNING AND ITS RELATIONSHIP TO ACHIEVEMENT IN AUTOMATED ANALYSIS CHEMISTRYFOR STUDENTS OF THE SCIENCE DEPARTMENT - Dr.Zhraa Raouf Jawad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to delve into self-regulated learning and knowledge acquisition and its relationship with the scholastic achievement of basic sciences students. The research sample consisted of 60 male and female senior students majoring in organic chemistry in the 2019-2020 academic year. In relation to the research instrument, the researcher employed Ahmad’s (2007) self-regulated learning scale and administered it to her own sample having insured its reliability and validity.The results revealed that the research sample enjoyed a high level of self-regulated learning. Likewise, there was a relationship between this kind of learning and scholastic achievement regarding the organic chemistry field. These results gave birth to some conclusions and recommendations. For example, the syllabus design, teacher development, and teacher training programs of universities should be based on self-regulated learning. Future studies are also suggested to conduct similar investigations by replicating the current research on other samples and educational levels to uncover the relationship between self-regulated learning and other variables.